2014
DOI: 10.2147/dddt.s60187
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal fentanyl for pain due to chemoradiotherapy-induced oral mucositis in nasopharyngeal cancer patients: evaluating efficacy, safety, and improvement in quality of life

Abstract: This study evaluated the efficacy, safety, and quality of life (QoL) measure of transdermal fentanyl (TDF) for moderate-to-severe pain due to oral mucositis caused by chemoradiotherapy in patients with advanced nasopharyngeal carcinoma (NPC). Patients with NPC who experienced moderate-to-severe oral mucosal pain during chemoradiotherapy (n=78) received TDF for pain relief. Pain relief and QoL were compared before and after treatment. The mean numeric rating scale score was reduced from 7.41±0.96 before treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Fentanyl may be effective to treat pain due to OM in patients treated with CT, with or without RT [50]. A single-center study showed that transdermal fentanyl reduces the mean pain scores when administered at 25 μg/h during CT-RT [137].…”
Section: A Comprehensive Managementmentioning
confidence: 99%
“…Fentanyl may be effective to treat pain due to OM in patients treated with CT, with or without RT [50]. A single-center study showed that transdermal fentanyl reduces the mean pain scores when administered at 25 μg/h during CT-RT [137].…”
Section: A Comprehensive Managementmentioning
confidence: 99%
“…In patients with severe mucositis caused by aggressive cytotoxic anticancer agents administered during the conditioning regimen, fentanyl patch is a more convenient method of pain management than morphine injection and is a better option than sustained-release oral medication because of the severe oral pain experienced by these patients. Recent studies have indicated that fentanyl patch is an effective tool for the management of pain associated with oral mucositis caused by chemotherapy and is also a noninvasive application compared to injections, especially in immunosuppressed patients [ 26 , 27 ]. However, the lowest-dose fentanyl patch that can be used is 12 µg/h, which is equivalent to 10 mg morphine injection.…”
Section: Discussionmentioning
confidence: 99%
“…An early study examining the time trends and characteristics of prescribing opioids for patients with a variety of cancers, showed that fentanyl was prescribed 10.2% of the time during the last 3 months, particularly in head and neck cancer cases using transdermal patches on most occasions. The efficacy, safety, and quality of life of head and neck cancer patients using fentanyl transdermal patches were also evaluated in a variety of prospective studies to show a significant decrease in pain, a better quality of life, and reduced side effects, the most common being nausea and vomiting [ 80 , 81 , 82 ]. However, there is a lack of studies that compare Fentanyl transdermal patches with other opioid analgesics [ 79 ].…”
Section: Transdermal Drug Deliverymentioning
confidence: 99%